Depression and Reasoning Ability in Adolescents: Examining the Moderating Role of Growth Mindset - Hu, Chen; Wang, Cuicui; Liu, Weiwei; Wang, Daoyang (Frontiers in Psychology, 2022)
The present two-year longitudinal study aimed to examine the relationship between depression and reasoning ability in adolescents, and further investigated the modulation effect of growth mindset on this relationship. A total of 1,961 and 1,667 Chinese adolescents participated in the study for the first year (T1) and second year (T2), respectively. The results showed that T1 depression was negatively correlated with T1 growth mindset (r = -0.35, p < 0.001), T1 reasoning (r = -0.30, p < 0.001), and T2 reasoning (r = -0.23, p < 0.001). Regression analysis revealed that T1 depression and the interaction between T1 depression and T1 growth mindset significantly predicted T1 reasoning (β = -0.220/-0.044, all ps < 0.05). After controlling for gender, age, family socioeconomic status, and T1 reasoning ability, both T1 depression and the interaction between T1 depression and T1 growth mindset still significantly predicted T2 reasoning (β = -0.104/β = 0.054, all ps < 0.05). The simple slope analysis found that the negative correlation between depression and reasoning in the high growth mindset group was weaker than that of the low growth mindset group in both T1 and T2, suggesting that growth mindset plays a significant moderating role in the relationship between depression and reasoning. In conclusion, depression was negatively correlated with reasoning ability in adolescents, in addition, growth mindset moderated the relationship between depression and reasoning.